Histomorphometric and Histopathologic Evaluation of the Effects of Systemic Fluoride Intake on Orthodontic Tooth Movement - Zorlu, Fatma Yalcin; Darici, Hakan; Turkkahraman, Hakan (European Journal of Dentistry, 2019)
Objectives The aim of this study was to determine the effects of systemic fluoride intake on orthodontic tooth movement with histomorphometric and histopathologic methods.Materials and Methods Forty-eight Wistar albino rats were randomly divided into four groups of 12 rats each. Group I received fluoridated water and underwent orthodontic tooth movement. Group II received fluoridated water and did not undergo orthodontic tooth movement. Group III received nonfluoridated water and underwent orthodontic tooth movement. Group IV received nonfluoridated water and did not undergo orthodontic tooth movement. At the beginning of the experiment (T1), impressions were taken from the maxilla of the rats in groups I and III under general anesthesia, and a NiTi closed coil spring appliance was ligated between the left maxillary central incisors and maxillary first molar. The orthodontic force applied was approximately 75 g, and the duration of the experimental period was 18 days. During the experimental period, appliances were controlled daily. At the end of the experimental period (T2), the rats were sacrificed with an overdose of a ketamine/xylasine combination, and their impressions were obtained. The upper first molars were subsequently dissected for histological examination. Incisor–molar distance, number of osteoblasts, number of osteoclasts and periodontal ligament (PDL) space widths on the compression and tension sides were measured.Statistical Analysis All measurements were statistically analyzed with SPSS for Windows version 18.0 (SPSS Inc., Chicago, IL, USA). Repeated measures ANOVA and posthoc Tukey tests were used to compare the groups.Results No statistically significant difference was found with respect to the amount of tooth movement between the fluoridated and nonfluoridated groups (p > 0.05). Orthodontic force application increased the number of osteoblasts at the tension sides and reduced it at the compression sides (p < 0.001). An increased number of osteoclasts was observed in the nonfluoridated group relative to the fluoridated group (p < 0.01).Conclusions No difference was observed with respect to the amount of tooth movement between the fluoridated and nonfluoridated groups. Fluoride significantly reduced the number of osteoclasts in the experimental groups.
Keywords: fluorosis; orthodontic tooth movement; root resorption; histomorphometry